Extraction and Purification of Chitosan from Chitin Isolated from Sea Prawn (Fenneropenaeus indicus) - Paul, Sneha; Jayan, Aiswarya; Sasikumar, Changam Sheela; Cherian, Sanjay M (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Chitosan is an amino polysaccharide prepared by processing prawn waste (shell) which involves the demineralization, deprotienization and deacetylation. Chitosan is a versatile natural polysaccharide, its second most abundant natural polymer. Researchers have found that chitosan as biocompatible, biodegradable and non-toxic, which have made wide applicability in the pharmaceutical field. The main study focuses on the purification of chitosan from chitin isolated from Fenneropenaeus indicus, will be suitable for the pharmaceutical industry. The chitosan yield was found to be 57.69%, and it was analyzed for its physiochemical parameters, antibacterial and antifungal activity. Keywords: Chitosan, Chitin, Natural polymer, Characterization, Purification, Physiochemical parameters, Antibacterial, Antifungal activity.